A importância da qualidade do balanço social na gestão de negócio: uma contribuição para aplicação em instituições educacionais privadas de ensino superior - Garcia, Carolina Oliveira (2002)
The main objective of the present work is to contribute with a model of Social Balance that may assist the segment of Higher Educational Private Institutions. The analysis and the popuiarization concerning its importance are necessary for evaluating the Quality of SB in the business administration of said Institutions. We are aware of government flaws when it comes to meeting expectations of the community s requirements. Therefore, the Social Balance should be rendered as basis for an unequivocal demonstration of the result of the social actions diagnosed as social accountability. We have been objectively evaiuating the Social Balance as settlement of accounts regarding the acts and facts of the social actions exercised by a company. Any lack of compromise with its actual accountability is liable to appear to us as evidence of unconcem for factual aspects. The Social Balance must inform what has actually been done, what should have been done and what still lies ahead to the accornplishment of its relevant role in totun-/ . Under no circurnstances should the use of the Social Balance be used with the purpose of neutralizing actions that might cast a shadow over the disclosure of the social liabilities of companies, masking them into negative acts on behalf of mankind and of the environrnental patrimony. Such masking of a Social Liability, often to the extent of rendering it irretrievable, will be considered at ali times and circumstances as deeply discrediting and even as a criminal deed. The recognition of the legal instruments purporting to instruct and tend an ethicai behavior should be considered as a healthy yoke, which also rewards the Social Balance, which imparts to it this very sarne reality. Controversy makes the Social Balance to resemble a financial one, wherein the total figure of spent monies on activities labeled as social by the company is disclosed. We may consider that the Social Balance for Higher Educational Institutions is a matter of moraiity regarding Education. For such reason we are to defend the need for expansion of the Social Balance in Education through SAE - Social Accountability in Education, bearing in mmd that alI things acquired by knowledge are to be iooked upon as culture. Therefore, it is undeniable that whatever project developrnent carried out with direct participation and operation by the alumni is a tool of irrefutable importance in the marketing strategy.